A social welfare function characterizing competitive equilibria of incomplete financial markets - Mario Tirelli; Sergio Turner (Brown University, Department of Economics, 2008)
A classic characterization of competitive equilibria views them as feasible allocations maximizing a weighted sum of utilities. It has been applied to establish fundamental properties of the equilibrium notion, such as existence, determinacy, and computability. However, it fails for economies with missing financial markets. We give such a characterization for economies with missing financial markets, by an amended social welfare function. Its parameters capture both the relative importance of households' welfare-the classic weights-as well as the disagreements among them as to the value of the missing markets. As a by-product, we identify the dimension of the set of interior equilibrium allocations.
Keywords: D52; D61; 330; incomplete markets; social welfare function; manifold